Correspondence from Dan Bryan, Joseph Gallagher and Moss Twomey to Florence O'Donoghue regarding Gallagher's 'Sunday People' series on relations betweeen Ireland and Germany in the Second World War, - Gallagher, Joseph P., journalist (1962)
Also includes letter from Mick Costello regarding perceptions of Irish allegiance during World War II, and extracts from Enno Stephan’s 'Secret mission - Ireland' in 'Sunday Review', with related notes,